Acclimating to thermal changes: Intraspecific variation in a small mammal from the Andes Mountains - Sassi, Paola Lorena (2015)
Ambient temperature strongly affects an ecosystem's characteristics as well as the attributes of individuals, eventually determining the distribution of populations and species. Phenotypic plasticity plays a central role in the administration of energy under thermal variation through traits underlying energy acquisition and expenditure. A powerful approach to assess acclimation ability to environmental variation is studying relevant traits along natural geographic gradients. Our goal was to assess and quantify in the small rodent Phyllotis xanthopygus, changes in traits relevant to energy balance in response to its thermal landscape. We compared energy intake and digestibility by animals from sites at different elevations under different temperatures in the laboratory. Results showed an increase in energy acquisition rates by the lower-elevation individuals to cope with low temperatures, while high-elevation animals appeared unaffected by this treatment. After acclimating to warmer conditions, all individuals showed a similar decrease in energy intake, irrespective of their origin site. We also assessed thermal conductance in individuals from different elevations and found that animals from higher sites exhibited lower heat loss rates. Our evidence suggests that heat conservation differences could in part account for differences among high and low elevation animals in the ability to cope with low temperatures. The lack of plasticity under the warm thermal treatment conforms to recent reports of high conservatism on the upper limit of the thermoneutral zone. P. xanthopygus displays intraspecific variation in the response to temperature, and we propose that this is highly relevant to model its chances in a warming environment.